The Terraform book - Turnbull, James (Turnbull Press, 2016)
Updated for Terraform 0.11! A hands-on, introductory book about managing infrastructure with HashiCorp's Terraform tool. Start small and then build on what you learn to scale up to complex infrastructure. Written for both developers and sysadmins. Focuses on how to build, test and run infrastructure and applications with Terraform and integration with tools like Consul. The book contains: Chapter 1: An Introduction to Terraform Chapter 2: Installing Terraform Chapter 3: Building our first application Chapter 4: Provisioning and Terraform Chapter 5: Collaborating with Terraform Chapter 6: Building a multi-environment architecture Chapter 7: Infrastructure testing.